Photothermal Driven Biomimetic Actuator Based on Asymmetric Microstructure Nb2CTx MXene Film - Nan Li; Tong Sun; Chenchu Zhang; Guangyou Fang; Yisen Wang (Advanced Electronic Materials)
Abstract The complex preparation process and low sensitivity have hindered the further application of current MXene‐based biomimetic actuators. In this paper, a photothermal biomimetic actuator based on an asymmetric niobium carbide (Nb2CTx) MXene film is prepared using the solution casting method, enabling interactions with various environments. Nb2CTx absorbs incident photons to provide an energy basis for the deformation of the actuator. Polyvinylidene fluoride (PVDF) with excellent film‐forming properties is used to overcome the brittleness of Nb2CTx to improve the flexibility of the film. Additionally, polyethylene (PE) film can increase the coefficient of thermal expansion (CTE) difference between the materials, providing a mechanical basis for the actuator's deformation. The actuator can respond quickly at low optical power density conditions and produce large bending angles (202° in 2.72 s). It also shows excellent performance in applications such as flexible crawling robots (30 mm in 54 s), smart mechanical clamps (lifting objects ten times their own weight), and smart lighting systems (multi‐light source response). These results not only demonstrate the immense potential of PE/PVDF/MXene composites in biomimetic actuation but also provide new inspiration for exploring the application of other types of MXene in this field.